Arab Relief Institutions Operating in Africa, their Poverty -Resistant Developmental Role:Kuwaiti Social Reform Association, and their Efforts in Djibouti as a Model - Mohamed Abdelfattah Tohamy Abdelfattah Tantawy; Ali Nasser Al-Tahitah (Usuli Faqih Research Centre PLT, 2024)
Vol. 31 No. 1